Foucault, the Subject and the Research Interview: A Critique of Methods - Fadyl, Joanna; Nicholls, David (John Wiley & Sons, 2013)
Research interviews are a widely used method in qualitative health research and have been adapted to suit a range of methodologies. Just as it is valuable that new approaches are explored, it is also important to continue to examine their appropriate use. In this article, we question the suitability of research interviews for 'history of the present' studies informed by the work of Michel Foucault - a form of qualitative research that is being increasingly employed in the analysis of healthcare systems and processes. We argue that several aspects of research interviewing produce philosophical and methodological complications that can interfere with achieving the aims of the analysis in this type of study. The article comprises an introduction to these tensions and examination of them in relation to key aspects of a Foucauldian philosophical position, and discussion of where this might position researchers when it comes to designing a study.
Keywords: Humans; Interviews as topic; Nursing research; Philosophy; Nursing; Qualitative research; Research design